Basic aspects of hearing: physiology and perception - Moore, Brian C. J.; Patterson, Roy D.; Winter, Ian M.; Carlyon, Robert P.; Gockel, Hedwig E. (Advances in experimental medicine and biology, 2013)
The International Symposium on Hearing is a highly-prestigious, triennial event where world-class scientists present and discuss the most recent advances in the field of hearing research in animals and humans. Presented papers range from basic to applied research, and are of interest neuroscientists, otolaryngologists, psychologists, and artificial intelligence researchers. Basic Aspects of Hearing: Physiology and Perception includes the best papers from the 2012 International Symposium on Hearing. Over 50 chapters focus on the relationship between auditory physiology, psychoacoustics, and computational modeling